Transmission of SARS-CoV-2 Alpha Variant (B.1.1.7) From a BNT162b2-Vaccinated Individual. (20th July 2021) - Kernéis, Solen; Planas, Delphine; Imbeaud, Sandrine; Staropoli, Isabelle; Puech, Julien; Robillard, Nicolas; Rodary, Julien; Bruel, Timothée; Vieillard, Thomas; Schwartz, Olivier; Belec, Laurent; Péré, Hélène; et al.
Abstract: Cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) acquisition after vaccination with BNT162b2 have been described, but the risk of secondary transmission from fully vaccinated individuals remains ill defined. Herein we report a confirmed transmission of SARS-CoV-2 alpha variant (B.1.1.7) from a symptomatic immunocompetent woman 4 weeks after her second dose of BNT162b2, despite antispike seroconversion.